PRODUCTION OF BIOETHANOL FROM SPIRULINA PLATENSIS BIOMASS VIA ACID HYDROLYSIS - Muyassaroh, Muyassaroh; Dewi, Rini Kartika; Anggorowati, Dwi Ana (jurnal ATMOSPHERE, 2026)
The problem faced by the world now is the rarity of fossil fuel resources availability such as oil and natural gas, so if not switching to other renewable resources the fossil resources shall run out soon. Hence, bioethanol becomes a promising alternative in the future. One of the fuel resources becoming a favorite that can be utilized as bioethanol is spirulina platensis. Bioethanol production with Algae-based material (Spirogyra sp.) firstly is the stage of acid hydrolysis process of cellulose into glucose using HCl, H2SO4, and HNO3 with acid concentration respectively 0.1 N; 1N; 2N under temperature 80 oC, 90 oC, 100 oC. It continued with the stage of glucose fermentation into bioethanol by adding urea, NPK, and yeast. Next, for bioethanol purification is distillation process under temperature 78 for 4 hours. The result showed that the highest ethanol content before distillation is 0.317695% and after distillation is 10,36% occurring in the concentration of 2N H2SO4 under temperature 100 oC.